Discovery of BI 135585, an in vivo efficacious oxazinanone-based 11β hydroxysteroid dehydrogenase type 1 inhibitor. Issue 14 (15th July 2017) - Zhuang, Linghang; Tice, Colin M.; Xu, Zhenrong; Zhao, Wei; Cacatian, Salvacion; Ye, Yuan-Jie; Singh, Suresh B.; Lindblom, Peter; McKeever, Brian M.; Krosky, Paula M.; Zhao, Yi; Lala, Deepak; et al.
Graphical abstract: Abstract: A potent, in vivo efficacious 11β hydroxysteroid dehydrogenase type 1 (11β HSD1) inhibitor (11j ) has been identified. Compound11j inhibited 11β HSD1 activity in human adipocytes with an IC50 of 4.3 nM and in primary human adipose tissue with an IC80 of 53 nM. Oral administration of11j to cynomolgus monkey inhibited 11β HSD1 activity in adipose tissue. Compound11j exhibited >1000× selectivity over other hydroxysteroid dehydrogenases, displays desirable pharmacodynamic properties and entered human clinical trials in 2011.